Teachers’ Perception of Disposition in English Language Teaching English at Junior High School - Erni; Yuanita Putri; Dahnilsyah; Aulia Agustiani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Disposition influences teachers’ behaviour, which in turn impacts student learning, motivation, and development. Therefore, teachers' dispositions must be continuously developed to realise the competencies they possess. This study employed a mixed-methods approach to analyse teachers' perceptions of disposition in English language teaching at senior high schools in Dumai City, Riau Province, Indonesia. Forty-three teachers who enrolled in the English teacher centre were selected as respondents in this study through purposive sampling. The research instruments consisted of questionnaires and observation. The triangulation method and statistical analysis were applied to assess data validity and reliability. The descriptive statistic was applied for the quantitative data analysis, and thematic analysis was applied for the qualitative data analysis. The findings revealed that the average score of teachers’ perceptions of disposition was 3.02, which is categorised as moderate. The results indicate that teachers generally have positive perceptions of disposition in English language teaching. However, the observation data showed that teachers still pay limited attention to the implementation of disposition in classroom practices. Therefore, teachers’ dispositions need to be further developed to actualise the competencies they possess. Considering that most students currently utilise artificial intelligence (AI) in learning English, program evaluation and training are necessary to strengthen teachers' dispositions in English language teaching.